Nuevo enfoque de la educación inclusiva y su articulación con la práctica docente y no docente - Toral Ganoza, Patricia Beatriz (2019)
Inclusive education is an urgent need in the Peruvian educational system. The Education Act states that this is a right for all without distinction, however education for children with special abilities have been locked up in special schools, limiting participants to a confined education, avoiding social interaction with peers and socialization in their midst. The research presented aims to provide input regarding the updating of teaching and non-teachers working in special and basic education in regular primary education, it is proposed a training program in Inclusive Education and its new approach to help to overcome the condition of children with special educational needs for social integration.